Impact of extraction techniques on phytochemical composition and bioactivity of natural product mixtures - Sun, Shicai; Yu, Ying; Jo, Yunju; Han, Jung Ho; Xue, Yingqi; Cho, Minkyoung; Bae, Sung-Jin; Ryu, Dongryeol; Park, Wonyoung; Ha, Ki-Tae; Zhuang, Shiwei (Frontiers in Pharmacology, 2025)
Extraction methods critically influence the phytochemical profile and bioactivity of natural product mixtures, affecting their efficacy as therapeutic agents. This review assesses the impact of various extraction techniques—such as solvent-based extraction, ultrasound-assisted extraction, and enzymatic extraction—on the composition of bioactive compounds in plant extracts. We discuss how extraction parameters modify the bioactivity profiles, influencing their application in pharmaceutics and nutrition. This review critically analyzes these techniques with a special focus on integrated (hybrid) strategies, revealing that while advanced methods like ultrasound-assisted extraction and microwave-assisted extraction offer improved efficiency, the greatest potential lies in the synergistic combination of methods to maximize yield and preserve bioactivity. The insights gathered here aim to guide researchers in developing optimal and sustainable extraction protocols for therapeutic applications.